TEACHER’S INSIGHTS ON PSYCHOLOGICAL AND SOCIAL WELL-BEING OF STUDENTS WHO STUTTER IN INCLUSIVE SCHOOLS IN ASTANA - Shaken, Madina (Nazarbayev University Graduate School of Education, 2025)
The role of the teacher is ubiquitous in the school life of students, not only as the academic authority but also as a key figure in shaping students’ social, emotional, and psychological development, by fostering an environment where the students can succeed both intellectually and personally. However, teachers who teach students with special needs, notably students who have a speech disorder such as stuttering, have a significantly higher influence on their school life, as students who stutter need to engage in speaking in both academic and social settings. Since psychological and social well-being of the students who stutter is considered one of the indicators of inclusion, there is a need for teachers’ awareness about the student’s psychosocial well-being in order to foster safe learning environment. Teacher’s experiences working with students who stutter with a focus on their psychosocial well-being have not received sufficient attention in Kazakhstan. Consequently, there is a research gap on experiences of teachers working with students who stutter, particularly the challenges teachers face, their understanding of students’ well-being, and the strategies they implement to cope with barriers encountered during the lesson. Therefore, the present qualitative phenomenological research aimed to explore the insights of eight teachers on psychological and social well-being of students who stutter at inclusive schools, based on their experience. Data was collected through semi-structured interviews and the analysis was guided by the Conceptual Model of Psychological and Social Well-being (Keyes, 1998; Ryff, 1989) which was used as the framework for understanding the well-being components of students who stutter. The teachers in this study reported positive experiences by employing inclusive approaches and forming strong collaborations with parents of students who stutter. Nevertheless, with regard to students’ well-being, teachers reported challenges such as low self-esteem, low involvement in leadership roles, and reduced participation in class activities. In response to these challenges, teachers shared diverse coping strategies to better accommodate and support students who stutter. The findings highlight the importance of navigating classroom engagement, promoting positive peer relationships, and encouraging active participation, which can enhance students' academic and social experiences. Additionally, the study emphasizes the role of parental support in sustaining the psychological and social well-being of students who stutter.
Keywords: Type of access: Open access; students who stutter; teacher experience; psyhological well-being; social well-being; Kazakhstan